Characterization of a Putrescine Transaminase From Pseudomonas putida and its Application to the Synthesis of Benzylamine Derivatives - Galman, James L.; Gahloth, Deepankar; Parmeggiani, Fabio; Slabu, Iustina; Leys, David; Turner, Nicholas J. (Frontiers in Bioengineering and Biotechnology, 2018)
The reductive amination of prochiral ketones using biocatalysts has been of great interest to the pharmaceutical industry in the last decade for integrating novel strategies in the production of chiral building blocks with the intent of minimising impact on the environment. Amongst the enzymes able to catalyse the direct amination of prochiral ketones, pyridoxal 5’-phosphate (PLP) dependent ω-transaminases have shown great promise as versatile industrial biocatalysts with high selectivity, regioselectivity and broad substrate scope. Herein the biochemical characterisation of a putrescine transaminase from Pseudomonas putida (Pp-SpuC) was performed, which showed an optimum pH and temperature of 8.0 and 60°C, respectively. To gain further structural insight of this enzyme, we crystallised the enzyme in the apo-form and the structure determined to 2.1 Å resolution which revealed a dimer that adopts a class I transaminase fold comparable to other class III transaminases. Furthermore we exploited its dual substrate recognition for biogenic diamines (i.e., cadaverine) and readily available monoamines (i.e., isopropylamine) for the synthesis of benzylamine derivatives with excellent product conversions and extremely broad substrate tolerance.